Kondisi Tempat Tumbuh dan Simpanan Karbon Diatas Permukaan Tanah pada Tegakan Jati di Taman Wisata Alam Camplong Provinsi Nusa Tenggara Timur - Pathibang, Meilyn Renny; Matatula, Jeriels; Aryani, Ni Kade Ayu Dewi; Selanno, Frenly Marvi; Oktaviani, Eva; Silaban, Rosalia; Almulqu, Aah Ahmad; Kleruk, Flora Evalina; Wardhana, Laurentius D. Wisnu; Lamanda, Sukriati Andesti; Rusadi, Nusrah; Nababan, Badia Roy Ricardo (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Forests store biomass and carbon in the form of living trees, forest floor detritus (e.g. litter falls), soil and wood products. This study describes inventory results of the above ground biomass of teak (Tectona grandis L.f.). By determining the site condition and developing allometric method, the inventory was designed to estimate the potential of above ground biomass of teak. This study aims to determine the characteristics or site qualities, carbon stock and find out whether the characteristics of the soil has a high or low correlation to the carbon stored in teak forest in Taman Wisata Alam Camplong, East Nusa Tenggara Province. Carbon stored in teak forests are 45.53 ton/ha and 104.35 ton/ha for IV and V age classes, respectively. The correlation between soil characteristics and carbon stock is obtained that the P and K soil has a positive correlation to carbon stock in the teak forest. The equation model for the relationship between growing conditions and aboveground carbon stocks is Y=25.182-4.149X1-172.231X2 + 2.046X3 + 32.711X4 + 0.297X5-28.330X6-1.746X7 +0.171X8.